BODY IMAGE EFFECT ON THE BEHAVIOR OF BEAUTY PRODUCTS IMPULSE PURCHASES ON THE STUDENTS PSYCHOLOGY AL AZHAR UNIVERSITY OF INDONESIA - Faisal Rachmat (Al-Mubin, 2022)
ABSTRACT – The research aims at understanding the body image factors affecting behavior impulsive among the girls who still relatively into final stages development of teenager. Consumer behavior sometimes did not involve consideration why and the reason someone has to have that products, and tending to implicate desire spontaneous and unreflective to purchase, it is a form of impulsive buying behavior. The impulsive buying related characteristic of the body image who are only some of the concept of self with regard to the physical properties. Teenagers more sensitive to physical picture so as to drive them do a variety of physical effort to turn the appearance of their social community in accordance with the demand. This research using quantitative methods, with nonprobability sampling use accidental sample. Analysis of data in this research using analysis of multiple regression, where this analysis used to know how big independent variable influence on dependent variables. The research was conducted in Al Azhar University of Indonesia especially in female student of psychology. The results of that could be observed in this research is that there a significant negative influence of between the body image to every the impulsive buying behavior of beauty product on female student of psychology in Al Azhar University of Indonesia. The influence of the body image at 40,4 % respectively to the buying impulsive behavior. Table fcount as much as 26,244 and obtained table distribution f as much as 2,68 with significant 0,05. The result stated that 26,244 > 2,68, so that it can be said that the body image to have an influence a significant impact on the impulsive buyer.